A micro-Raman and X-ray study of erupted submarine pyroclasts from El Hierro (Spain) and its' astrobiological implications. (May 2019) - Lalla, E.; Sanz-Arranz, A.; Lopez-Reyes, G.; Cote, K.; Daly, M.; Konstantinidis, M.; Rodriguez-Losada, J.A.; Groemer, G.; Medina, J.; Martínez-Frías, J.; Rull-Pérez, F.
Highlights: Pyroclastic floating pumice as possible extremophile habitats in the emergence of life on Earth. The significance of hydrothermal volcanic activities for the evolution of life. Raman analysis of pumice samples from submarine volcanic eruptions from La Restinga, Spain. Vibrational identification of new undetected minerals in La Restinga volcanic eruption, Spain. The relevance of the Raman spectroscopy for planetary exploration in Martian missions. Abstract: The pumice volcanic samples could have possible connections to the evolution of life and give us insight about their bio-geochemical processes related. In this regard, the samples from the volcanic eruption from La Restinga (El Hierro, Spain) in 2011 have been mainly studied by means of Raman spectroscopy. The research also includes analysis of XRD, Scanning Electron Microscopy and Optical Microscopy to support the Raman analysis. The results show that the Raman methods and mineral analyses are in strong agreement with the results obtained from other authors and techniques. The internal white foamy core (WFC) of the studied pumice samples shows amorphous silica, Fe-oxides, Ti-oxides, quartz, certain sulfates, carbonates, zeolites and organics. On the other hand, the external part (dark crust – DC) of these samples mainly presents primary-sequence mineralogy combined with some secondary alteration minerals such as olivine, feldspar, pyroxene, amorphous silica, and Fe-oxide. Raman spectroscopy detected other minerals not yet reported on these samples like barite, celestine and lepidocrocite. Also, the different chemometric and calibration methods for Raman spectroscopy in elemental composition, mineral classification and structural characterization has been successfully applied. From the astrobiological perspective, the research was also complemented with comparisons to other similar samples from terrestrial analogs. The main consideration was taking into account the proposed hypothesis regarding the potential behavior of the pumice as a substrate for the evolution of life. Furthermore, the detailed analysis from La Restinga eruption is coherent with the mineral phases and processes discussed from previous literature. The white internal part fulfills the conditions to work as an organic reservoir, confirmed by the detection of organic matter and selected minerals that could be used as energy sources for bacterial communities. The external layers of the samples work as a shielding layer to protect the organics from decay in extreme conditions. Finally, here we have demonstrated that the characteristics and advantages of Raman spectroscopy could help to assess and understand the possible biogenicity and alteration processes of any geological sample to be found on Mars.